Spinels of Variscan olivine hornblendites related to the Montnegre granitoids revisited (NE Spain): petrogenetic evidence of mafic magma mixing - G. GALÁN; P. ENRIQUE; L. BUTJOSA; M. FERNÁNDEZ-ROIG (Geologica Acta, 2017)
Olivine hornblendites (cortlandtites) form part of the Montnegre mafic complex related to late-Variscan I-type granitoids in the Catalan Coastal Ranges. Two generations of spinel are present in these hornblendites: Spl1 forms euhedral crystals included in both olivine and Spl2. Spl2 forms euhedral to anhedral crystals associated with phlogopite and fibrous colourless amphibole forming pseudomorphs after olivine. Compositions of Spl1 are picotite-Al chromite (Fe#: 77.78-66.60; Cr#: 30.12-52.22; Fe3+/R3+: 6.99-21.89; 0.10< TiO2%< 0.62). Compositions of Spl2 are pleonaste (Fe#: 37.86-52.12; Cr#: 1.00-15.45; Fe3+/R3+: 0.31-5.21; TiO2% <0.10%). The two types of spinel follow a CrAl trend, mainly due to the substitution (Fe2+)-1Cr-1= MgAl, which is interpreted as the result of mixing between two different mantle-derived melts. The compositions of early Spl1 crystals included in olivine are characteristic of Al-rich basalts. More aluminous Spl2 would result from reaction of olivine with a less evolved, Al and K-rich mantle-derived melt after new refilling of the magma chamber or channel. As a whole, spinels from similar examples of Variscan olivine hronblendites also follow a CrAl trend with high Fe# and starting at higher Cr# than other trends of this type. Cr# heterogeneity in the early spinels from these Variscan hornblendites would be inherited from the variable Al content of the mafic melts involved in their genesis.